FACTORS THAT AFFECT THE PROFABILITY OF CONVENTIONAL BANKS OF BATAM CITY - Cuandra, Fendy; Setiawan, Iwan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The main purpose of this study is to analyze factors that affect the profability of conventional banks of Batam city with the influence of capital adequacy ratio, non performing loan, loan to deposit ratio, BOPO, and net interest margin of return on asset during of period 2014-2019. This study is quantitative method from secondary data with the object of research as many as 27 banks conventional of Batam city.